PENGABDIAN KEPADA MASYARAKAT MELALUI KEGIATAN KEAGAMAAN, SOSIAL, DAN BUDAYA DI BEBERAPA PURA DI JAWA TIMUR - Putri Anggreni; I Gusti Ayu Suasthi; Wayan Paramartha (UNHI Press, 2026)
Community service activities are one of the manifestations of the Tri Dharma Perguruan Tinggi (Three Pillars of Higher Education), which aim to make a tangible contribution to society. One form of service that is relevant to the local wisdom of the Balinese people is religious and social activities at several temples in East Java. These activities include participations in communal prayers,